Frederick Tschopp, Landscape Architect, OE in New Zealand 1929-32 - Humphris, Adrian; Mew, Geoff (Architectural History Aotearoa, 2021)
Frederick Tschopp was a naturalised American of Swiss birth who had trained as a horticulturalist specialising in landscape architecture. He and his wife arrived in Auckland in September 1929 and he soon found work with some of the local bodies there. Works and Development in Wellington later employed him in designing gardens for several important government properties. This was not a permanent position however and about July 1931 he moved to Rotorua with a major contract to beautify the city, including extensive street plantings and an upgrade of the lake shore. Most of this work was well-received but there were some dissenting voices. The contract was terminated in November 1932, but with several goodwill gestures. While in Rotorua, Frederick had visited both Hamilton and Tauranga, commenting on landscape design aspects. The family (now with the addition of a son) left New Zealand for home in Los Angeles in late November 1932. Frederick had a subsequent career with the Department of Water in California and died at Laguna Hills, Orange, California in February 1980. The reasons for Tschopp's visit to New Zealand can be interpreted in two ways. Clearly the newspapers regarded him as an overseas expert with a talent for landscape design, still a fairly new concept in the country in the late 1920s. He undoubtedly stood out as an American with drive and initiative. But he was only 24 when he first arrived, and his motives may well have been to gain overseas experience (OE) to help his chances of obtaining a lucrative job on his return to America. One paper described him as being in the course of a world tour but there is no conclusive evidence for him having spent long in other countries at this time.